2014
DOI: 10.1007/s13277-014-2469-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of TROP2 expression in patients with gallbladder cancer

Abstract: Altered expression of TROP2 is observed in various types of human cancers. However, the clinical significance and pathological role of TROP2 in gallbladder cancer (GBC) remains unclear. The main objective of this investigation was to clarify the relationships between TROP2 expression and the clinicopathological features of patients with GBC. Immunohistochemistry was performed to investigate the expression of TROP2 and epithelial-mesenchymal transition (EMT) indicator proteins in 93 patients with GBC. Immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Although Chen et al . revealed that TROP2 overexpression was associated with poor prognosis of GBC [ 16 ], TROP2 signal pathways and possible mechanisms are still unclear in GBC proliferation, migration and metastasis. We have previously characterized the cancer stem-like cells from GBC cells [ 17 ], and investigated their multidrug resistance [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although Chen et al . revealed that TROP2 overexpression was associated with poor prognosis of GBC [ 16 ], TROP2 signal pathways and possible mechanisms are still unclear in GBC proliferation, migration and metastasis. We have previously characterized the cancer stem-like cells from GBC cells [ 17 ], and investigated their multidrug resistance [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Chen et al performed immunohistochemistry to observe the expression of Trop2 and EMT marker in gallbladder cancer. The results indicated that high Trop2 expression was significantly associated with lower E‐cadherin expression and acquisition of expression of vimentin . In our previous study, we also found Trop2+/E‐cadherin−was expressed in breast cancer (BC) and was associated with lymph node status, metastasis, tumor‐node‐metastasis (TNM) stage, and ER−/PR−/HER2− expression.…”
Section: Introductionmentioning
confidence: 73%
“…TROP2 is found to be overexpressed in the majority of human epithelial cancers, including pancreatic cancer, gastric cancer, lung cancer, ovarian cancer, and colorectal cancers (10,14,32). Chen et al (33) investigated the expression of TROP2 and epithelial-mesenchymal transition (EMT) indicator proteins in 93 patients with gallbladder cancer (GBC) and demonstrated that increased expression of TROP2 in GBC is associated significantly with aggressive progression and poor prognosis. In another study based on clinical samples, Guan et al (34) found that overexpression of TROP2 could be an independent predictor for poor clinical outcome in nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%